Hydraulic Fracturing in Poland: A Regulatory Analysis - Justin P. Atkins (Washington University Global Studies Law Review, 2013)
Hydraulic fracturing, or “fracking,” is a process by which water and other materials are injected into a geologic formation at a high pressure. This process “induces fractures in the formation that stimulate the flow of natural gas or oil, thus increasing the volume of gas or oil that can be recovered from coalbeds, shales, and tight sands . . . .” Hydraulic fracturing has been used for nearly 70 years and has enabled energy companies to recover oil and natural gas resources previously thought to be unrecoverable. In the past several years, hydraulic fracturing has induced an increasing number of serious environmental, political, and social concerns. As a result, several countries have restricted hydraulic fracturing practices or even banned their use altogether. Poland, however, is not one of those countries—Polish leaders are seeking to rapidly develop hydraulic fracturing operations within their country. Additionally, Poland may have the largest shale gas reserves in Europe. As a result, Poland has become a very attractive destination for energy companies looking to expand their fracking operations.
Keywords: fracking; hydraulic fracturing; Poland; energy regulation; oil; gas